2008
DOI: 10.1016/j.aca.2008.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel detection reagent for simple and sensitive determination of trace amounts of formaldehyde and its application to flow injection spectrophotometric analysis

Abstract: In this paper, a novel detection reagent for formaldehyde determination is proposed, and is applied to a simple and highly sensitive flow injection method for the spectrophotometric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 34 publications
0
30
0
4
Order By: Relevance
“…Li et al proposed a method based on the reaction of FA with methyl acetoacetate in the presence of ammonia. Maximum sampling throughput was about 21 samples/h with small interference [22]. Weng et al demonstrated an on-chip microfluidic FA detection method.…”
Section: Detection Methodsmentioning
confidence: 99%
“…Li et al proposed a method based on the reaction of FA with methyl acetoacetate in the presence of ammonia. Maximum sampling throughput was about 21 samples/h with small interference [22]. Weng et al demonstrated an on-chip microfluidic FA detection method.…”
Section: Detection Methodsmentioning
confidence: 99%
“…It is the simplest aldehyde that is known by its systematic name methanol [1]. The growing importance of HCHO as a commercial reagent based on its many unique characteristics and its varied applications have created a definite need for a systematic and critical account of HCHO chemistry [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose HCHO and other carbonyl compounds are often collected by reaction with proper aqueous reagent [10,11] during coating on a suitable sorbent [12,13] or annular diffusion on denuder [14]. Finally the corresponding derivatives are analyzed by separating methods such as high performance liquid chromatography [10,12,14,15], membrane [16], capillary zone electrophoresis [11,17], or even spectroscopic techniques like UV-Vis absorption [11,12,18], fluorescence, [19][20][21], etc.…”
Section: Introductionmentioning
confidence: 99%
“…O monitoramento espectrofotométrico de SO 2 pode ser alcançado através de sua conversão a um cromóforo produzido com o corante [15][16][17][18][19][20]. De forma similar, a aplicação de protocolos experimentais apropriados, capacita a análise de distintos compostos, tais como, ácido pícrico, sacarina, fenil butazona e a droga Probenecida [21], metanol [22], bromato [23,24], brometo [25], SO 3 -2 [26,27], Formaldeido [28][29][30][31][32][33][34][35], H 2 S [36][37][38], o pesticida organoclorado endosulfano [39], substancias tensoativas [40], os metais ouro [41] e Paládio [42].…”
Section: Introductionunclassified